Factors Influencing Employee Turnover among TB/HIV Management Unit’s in Public Hospitals in Puntland State of Somalia - Hassan, Mohamed Mohamoud; Muiruri, Lillian; Kimemia, Fredrick (International Journal of Health Sciences, 2024)
Purpose: To examine the factors influencing employee turnover among TB/HIV management unit’s in public hospitals in the Puntland State of Somalia. It examined the influence of job satisfaction, promotion opportunities, top management and organisation commitment on employee turnover among TB/HIV management units. Methodology: A descriptive research design was used to study the target population of 806 healthcare workers who work in public hospitals in the Puntland State of Somalia. The study sample consist of 267 respondents selected from among the healthcare workers in these hospitals. The data was collected through structured questionnaires that were self-administered to the health workers. The collected data was quantitative and analyzed using descriptive techniques and statistical tools like SPSS (Version 26). The findings were displayed as tables, charts, percentages, and means. Multiple regressions and Karl Pearson's correlation coefficient was also utilized to determine the relationship between the independent and dependent variables. Findings: The study found that organization commitment, job satisfaction and promotion opportunities were significant factors influencing the employee turnover among TB/HIV management unit’s in public hospitals in Puntland state of Somalia with significant value of p=.000 each. Further, the study also found that top management was an insignificant determinant of the employee turnover among TB/HIV management units in public hospitals in Puntland state of Somalia with significance value of .081. Unique contribution to theory, practice and policy (recommendations): Theory: The study challenges traditional theories by demonstrating that organizational commitment, job satisfaction, and promotion opportunities are more significant than top management in influencing employee turnover within specialized healthcare units. It suggests that healthcare administrators should focus on enhancing job satisfaction and career advancement opportunities rather than solely relying on top management strategies to improve retention. Policymakers should implement strategies that bolster employee engagement and career development in public hospitals, as these factors are crucial for reducing turnover and improving service stability.